Analisis Marjin Pemasaran Telur Ayam Ras di Kecamatan Sinoa dan Kecamatan Tompobulu Kabupaten Bantaeng - Sumarni Baking; Siti Wardah; Amruddin Amruddin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
One of the agricultural sectors that has quite an important role in supporting the national economy is the livestock sub-sector, including large livestock, small livestock, poultry, and other types of livestock. Poultry farming, namely laying hens, produces eggs, which are widely consumed by all levels of society. Eggs are a source of protein needed by the body, so it is not surprising that they are a food in demand. The areas that are the center for producing purebred chicken eggs are the Sinoa District and the Tompobulu District. The study aimed to analyze the marketing channels and margins of purebred chicken eggs. This research was conducted in Bantaeng District with two sub-districts, Sinoa District and Tompobulu District, with 25 respondents, where 20 breeder respondents were determined purposively, and five traders were determined using the Tracing Method. The data collection techniques used were surveys, interviews, and documentation. The research results were analyzed using a descriptive approach to describe the marketing channels for purebred chicken eggs and analysis of marketing margins. The research results show three marketing channels used by laying hen breeders: (1) Channel I (Breeders – Consumers); (2) Channel II (Breeders – Retailers – Consumers); (3) Channel III (Breeders – wholesalers – Retailers – Consumers). Meanwhile, the margin in Channel I is not found because breeders sell directly to consumers. On Channel II, the margin is IDR 200.00/item. On Channel III, the margin is IDR 400.00/item. The average marketing margin for marketing channel II is IDR. 6,000.00/frame, and channel III is IDR 12,000.00/ frame. The difference in margins that occur in marketing channels II and III is caused by the number of marketing institutions involved in marketing eggs, where the longer the marketing channel, the more marketing institutions are involved, which results in a greater marketing margin.